LABORATORY AND CLINICAL STUDIES OF CEFOTAXIME IN PEDIATRIC FIELD - KAMIYA, HITOSHI; INOUE, MASAKAZU; TANIMOTO, YASUO; IZAWA, TADASU; SAKURAI, MINORU (CHEMOTHERAPY, 1980)
In vitro and in vivo effect of cefotaxime (HR 756, CTX) a newly synthesized cephalosporin was investigated in pediatric patients. MIC of cefotaxime was measured for clincally isolated bacteria obtained from these patients, and compared with that of other antibiotics. The results showed that MIC of cefotaxime was superior to that of cefazolin with P.aeruginosa, S.faecalis, Streptococcus group C and Streptococcus group G. The mean peak serum concentratoin was 27.83μg/ml and 56μg/ml respectively when it was given 12.5mg/kg and 50 mg/kg by intravenous injection. The transfer of cefotaxime to cerebrospinal fluid was demonstrated in two patients but further pharmacokinetic studies should be done. In vivo effect of single cefotaxime was observed in 18 children with various infections. Excellent effect was obtained in 12 cases, good effect in 5 cases and unevaluable in 1 case, with the effective ratio being 100%. No side effect was observed in 27 cases by use of cefotaxime.